Hubungan status sosial ekonomi keluarga dengan kegemukan pada remaja SMA di Denpasar - Anak Agung Gede Ari Nanda Bhaswara; Made Ratna Saraswati (E-Jurnal Medika Udayana, 2018)
Obesity (overweight and obesity) is a global problem that is associated with various metabolic diseases. The prevalence of obesity worldwide has increased annually. Thus the prevention of risk factors of obesity needs to be done, and adolescence is a time that is right for prevent the obesity in the future. The aim of this study was to determine the relationship between socioeconomic status of families with obesity in adolescents high school in Denpasar. The design of this research is the analysis of cross-sectional study of 233 high school students in Denpasar. Respondents filled out a questionnaire about the socio-economic status and confounding variable and measurement of BMI through a calculation of height and weight. Socioeconomic status families, confounding variable and BMI were analyzed with Chi-square test statistic. The Univariate results obtained 27.5 % of respondents are overweight , with a frequency of male by 35.06 % ; and female respondents reached 23.72 %. The bivariate analysis results obtained significant relationship (p = 0.025; OR = 2:00; 95% CI = 1.084 to 3.695). Besides breakfast habits and BMI had a significant relationship (p = 0.000; OR = 3.097; 95% CI = 1.674 to 5.732). The next test performed multivariate binary logistic regression method obtained only breakfast habits which have a significant relationship to obesity in adolescents (p = 0.000) whereas socioeconomic status did not (p=0.052). This study shows an association between socioeconomic status and obesity in adolescents in Denpasar. In addition there are breakfast habits variables that more influence to obesity compared with socioeconomic status. Keywords: Obesity, Overweight, BMI, Social-Economic, Adolescents.